2020
DOI: 10.1186/s12889-020-09262-8
|View full text |Cite
|
Sign up to set email alerts
|

Scaled-up nutrition education on pulse-cereal complementary food practice in Ethiopia: a cluster-randomized trial

Abstract: Background Improving children’s weight status through nutrition education (NE) for mothers about using pulses in complementary feeding has been demonstrated in pilot studies, but no effect on stunting was reported. The aim of the study was to assess the impact of a 9-month pulse-nutrition education program on improving mothers’ knowledge, attitude, and practices (KAP) towards pulses, as well as its effect on children’s diet diversity, and nutritional status. The NE was delivered by Health Extension Workers (HE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…We attributed improved knowledge of the pulse-based diet group to a greater awareness of pulses through education and receiving pulses in their meals over 16 weeks. Furthermore, we provided education about the benefits of adopting healthy lifestyle practices, including diet to all women as a standard of care [32], which likely contributed to improved attitudes of both groups about pulse consumption as a component of healthy dieting, similar to previous reports [39,[46][47][48][49]. In addition to improved pulse consumption behaviours, we have previously shown the benefits of pulse foods on cardiometabolic (e.g., dyslipidaemia, impaired glucoregulatory status) and reproductive (e.g., menstrual regulatory, hyperandrogenism, and ovarian morphology) derangements in women with PCOS following healthcare counselling and education [18,19].…”
Section: Discussionmentioning
confidence: 80%
“…We attributed improved knowledge of the pulse-based diet group to a greater awareness of pulses through education and receiving pulses in their meals over 16 weeks. Furthermore, we provided education about the benefits of adopting healthy lifestyle practices, including diet to all women as a standard of care [32], which likely contributed to improved attitudes of both groups about pulse consumption as a component of healthy dieting, similar to previous reports [39,[46][47][48][49]. In addition to improved pulse consumption behaviours, we have previously shown the benefits of pulse foods on cardiometabolic (e.g., dyslipidaemia, impaired glucoregulatory status) and reproductive (e.g., menstrual regulatory, hyperandrogenism, and ovarian morphology) derangements in women with PCOS following healthcare counselling and education [18,19].…”
Section: Discussionmentioning
confidence: 80%
“…A total of 23 studies were included, and of these, 14 were quasi-experimental studies, 74-87 and 9 were cluster randomised trials. [88][89][90][91][92][93][94][95][96] Four studies for EBF 77 83 85 91 and six studies for EIBF 77 79 80 85 86 91 showed that community-based and facility-based interventions delivered in the form of BCC (such as policy advocacy, interpersonal communication, community mobilisation and mass media campaigns) and health service strengthening had an impact on infants. Two studies for the introduction of complementary foods, 79 93 six studies for MDD 79 89 90 92 94 96 and three studies for MMF 88 89 92 indicated significant effects of BCC on infants and young children.…”
Section: Discussionmentioning
confidence: 99%
“…Tariku et al 90 showed interventions involving complementary feeding messages using the HBM model significantly increased the proportion of MDD (from 37.5% to 67.9%; p<0.05). End line survey results following the intervention of nutritional education and counselling, and recipe demonstrations by Muluye et al (67.0% vs 33.0%, p=0.034) 94 and Teshome et al (51.5% vs 43.3%; p=0.001) 96 showed significant differences in the proportion of MDD between intervention and control groups. The remaining four studies indicated that the proportion of MDD increased over the intervention period, but the effect was not significant.…”
Section: Minimum Dietary Diversitymentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, community-based studies related to germination have focused on testing community acceptability with mothers [ 37 , 38 ] through cooking demonstrations by Health Extension Workers (HEWs) [ 39 ]. These studies did not examine how best to upskill mothers and the broader community in the food processing skills required to produce ARF or the opportunities and challenges of scaling up skill development in the community using existing peer support networks.…”
Section: Introductionmentioning
confidence: 99%